2013
DOI: 10.1111/iji.12056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of death pathway genes FAS and FASL polymorphisms in chronic HBV infection

Abstract: This study was designed to determine the possible asssociation between selected FAS and FASLG polymorphisms and Hepatitis B virus (HBV) infection. FAS-670 G/A, FAS-1377 G/A, FASLG-844 T/C and FASLG IVS2nt-124 A/G polymorphisms were genotyped by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP). A total of age and sex matched 108 controls and a hundred chronic HBV patients were recruited to conduct a case-control study. FAS-670 polymorphism was associated with chronic HBV infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Several studies have shown that FAS -670 AA genotype and A allele were associated with liver diseases such as autoimmune hepatitis and development of cirrhosis ( 30 , 31 ), Liver graft rejection ( 32 ) and Hepatitis C ( 33 ). Zamani et al ( 34 ) showed that FAS-670 A/G polymorphism was associated with chronic HBV infection, while FASL IVS2nt-124 A/G polymorphism was not; also FAS -1377 G/A and FASL-844 C/T genotypes were likely to play a substantial role in HBV infection outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that FAS -670 AA genotype and A allele were associated with liver diseases such as autoimmune hepatitis and development of cirrhosis ( 30 , 31 ), Liver graft rejection ( 32 ) and Hepatitis C ( 33 ). Zamani et al ( 34 ) showed that FAS-670 A/G polymorphism was associated with chronic HBV infection, while FASL IVS2nt-124 A/G polymorphism was not; also FAS -1377 G/A and FASL-844 C/T genotypes were likely to play a substantial role in HBV infection outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of apoptosis contributes to various liver diseases such as hepatocellular carcinoma, viral and autoimmune hepatitis, ischaemia/reperfusion injury, toxic liver damage and acute liver failure [4][5][6][7]33]. After cholestatic injury, the initial insult can be directed towards hepatocytes and cholangiocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have identified that dysregulation of apoptosis is a principal contributor to the pathogenesis of various liver diseases [5][6][7]. In cardiac diseases, apoptosis is also important in modulating heart function, and interrupting apoptosis can attenuate or prevent heart failure [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, death of HBV-infected hepatocytes is thought to occur primarily through Fas-mediated killing. Soluble Fas (sFas) and soluble Fas ligand (sFasL) have been shown to inhibit hepatocyte apoptosis [4244] allowing for the persistence of HBV in hepatocytes [45]. The Fas pathway is also involved in the apoptosis of activated T cells as a mechanism to maintain peripheral tolerance.…”
Section: Introductionmentioning
confidence: 99%